Literatur Review: Hubungan Peer Group Education dan Dukungan Keluarga terhadap Perilaku Deteksi Dini Kanker Payudara dengan SADARI pada Remaja - Nabila Vebiana Soviadi; Sutanto Priyo Hastono (Universitas Faletehan, 2023)
Malignant tumors leading to breast cancer pose a serious threat to adolescents under the age of 17 with increasing cases of 8 to 10 in 2018. To prevent the spread of breast cancer, breast self-examination (BSE), known as SADARI in Indonesian, was introduced as a preventive measure. This study aimed to identify the relationship between peer group education and family support with BSE behavior among adolescents. Through a literature review, 10 relevant articles were found on Google Scholar and Pubmed database, spanning publication years from 2019 to 2023. These articles were selected based on criteria of reputable national and international journals, written either in English or in Indonesian, and employing cross-sectional study design and open access. The research findings indicated that peer group education and family support play a significant role in promoting BSE behavior in adolescents. Other factors such as knowledge, attitude, and information sources can also influence BSE behavior in adolescents. Therefore, a comprehensive approach of breast cancer prevention in adolescents should take into account various influencing factors to enhance the effectiveness of preventive efforts. Further research is encouraged to delve deeper into these factors, enabling the development of more precise and efficient breast cancer prevention strategies.